2020
DOI: 10.1111/jam.14965
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in Aeromonas species isolated from aquatic environments in Brazil

Abstract: Aim The current study was conducted to determine the antimicrobial resistance profile and genetic relatedness of Aeromonas sp. isolated from healthcare and urban effluents, wastewater treatment plant (WWTP) and river water. Methods and Results We detected the presence of genes conferring resistance to β‐lactam, quinolone and aminoglycoside. Multilocus sequence typing was carried out to differentiate the strains, and multilocus phylogenetic analysis was used to identify the species. A total of 28 cefotaxime‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 86 publications
1
10
0
1
Order By: Relevance
“…In southern Brazil, epidemiological studies conducted by our group have shown a gradual increase in antimicrobial resistance in hospitalized patients in the last 20 years ( 15 17 ). However, GES enzymes were not found ( 18 , 19 ). Although GES enzymes have already been reported in several countries, few studies have explored the genetic context of these ARGs, especially in Brazil.…”
Section: Introductionmentioning
confidence: 95%
“…In southern Brazil, epidemiological studies conducted by our group have shown a gradual increase in antimicrobial resistance in hospitalized patients in the last 20 years ( 15 17 ). However, GES enzymes were not found ( 18 , 19 ). Although GES enzymes have already been reported in several countries, few studies have explored the genetic context of these ARGs, especially in Brazil.…”
Section: Introductionmentioning
confidence: 95%
“…The study by Conte et al (2020) evaluated the presence of antimicrobial resistance genes in the bacterium Aeromonas spp., present in wastewater and hospital and domestic e uents, in the region of Curitiba, Paraná. The study found the presence of the bla CTX-M , bla TEM and bla GES genes.…”
Section: Identification Of Genes Associated With Bacterial Resistancementioning
confidence: 99%
“…Aeromonads are considered emergent pathogens and its detection in various diarrheal stool samples clearly shows they are not as far from clinical routine as other enteric microorganisms ( Li et al, 2015 ; Mohan et al, 2017 ; Mbuthia et al, 2018 ). Consequently, interest about the genus Aeromonas , which embraces 36 recognized species, has risen over the past years ( Fernández-Bravo and Figueras, 2020 ; Ahmed et al, 2021 ; Conte et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Aeromonas possess wide spectra of antibiotic resistance profile and occurrence of multi-resistant strains have already been reported ( Galler et al, 2018 ; Conte et al, 2021 ). As inhabitants of aquatic environments, these microorganisms can be used as ecological indicators of water pollution since they harbor antibiotic resistance genes obtained from wastewater effluents ( Baron et al, 2017 ; Grilo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%